AN ANALYSIS STUDENTS’ VOCABULARY THROUGH SONG AT THE FIRST GRADE STUDENTS’ OF ELEMENTARY SCHOOL BAITURRAHMAH PADANG - Gitri Utari; Feby Meuthia Yusuf; Yessy Marzona (Ekasakti Educational Scientific Journal, 2024)
This thesis discussed about an analysis of students’ vocabulary through song. This research was conducted at elementary school Baiturrahmah Padang, the academic year 2022/2023. The researcher conducted this research based on finding in the classroom. This research used descriptive research. The population in this research was 11 students at first grade of elementary school Baiturrahmah Padang. In taking the sample, the researcher used total sampling technique and the class wasselected as a sample with a total of 11 students. Most of students have moderate vocabulary. The instrument for collecting data was vocabulary test. In collecting the data, the researcher gave students a song and asked them to read and singwith loudly in order to analysis their vocabulary. In data analysis, researcher calculated the test by using vocabulary rubric score that was adopted from the teacher.